A preliminary survey of the corrosivity of water in South African gold mines - A. Higginson; M. Phil; R. T. White (The Southern African Institute of Mining and Metallurgy, 1983)
Samples of water that had been collected underground from eight gold mines in South Africa were subjected comprehensive analysis of the quality of the waters, and their corrosivity on mild steel was measured by the laboratory techniques of extrapolation from Tafel plots and of polarization resistance. The results indicate that, if such factors as pH, Langelier index, and degree of aeration are beyond certain specified limits, the corrosivity ofthe water is affected. The applicability of the corrosivity index in predictions ofthe degree corrosion is questioned. Suggestions are included for future work involving the fundamental characterization of the corrosivity of mine waters.